Revaluation of Mbelek and Lachièze-Rey scalar-tensor theory of gravitation to explain the measured forces in asymmetric resonant cavities - Minotti, Fernando Oscar (2017)
The scalar-tensor theory of gravitation proposed by Mbelek and Lachièze-Rey has been previously shown to lead to a possible explanation of the forces measured in asymmetric resonant microwave cavities. However, in the derivation of the equations from the action principle some inconsistencies were observed, like no need to vary the electromagnetic invariant in a scalar source term. Also, the forces obtained were too high, in view of reconsideration of the experiments originally reported and of newly published results. In the present work, the equations are re-derived using the full variation of the action, and also the constant of the theory re-evaluated employing the condition that no anomalous gravitational effects are produced by the Earth’s magnetic field. It is shown that the equations originally employed were correct, and that the newly evaluated constant gives the correct magnitude for the forces recently reported.